Enraizamento de estacas de Pinus caribaea var. hondurensis - M Brandi, Renato; de Barros, Nairam Félix (Revista Ceres, 2025)
Cuttings from secondary branches of Pinus caribaea var. hondurensis were collected in April from two years old "ortets', in Viçosa, Minas Gerais.